REVITALISASI KOMPLEKS SITUS BANTEN LAMA: MENANGANI WARISAN KOTA ISLAM DI INDONESIA - Mohammad Ali Fadillah (Jurnal Kebijakan Pembangunan Daerah, 2025)
Banten was one of the leading port cities in Southeast Asia in the 17th centuries. However, since the early 19th century, the city has lost its primary function, leaving only the ruins of various important buildings at the Banten Lama archaeological site. For nearly three decades, the government has built public facilities, but the results have not been optimal for the utilization of cultural heritage. This study aims to understand cultural heritage preservation policies and their relationship to the revitalization program of the Banten Lama area. To address this issue, library data collection and field observations have been conducted at the Banten Lama site. Using descriptive-analytical methods, cultural heritage preservation policies at both the national and regional levels will be analyzed and compared with each other. Archaeological and historical analysis of urban sites, buildings, structures and other cultural objects such as palaces, fortifications, mosques, settlements and canals in Banten Lama confirms the implementation of this policy.. This study is expected to produce dominant factors that will inspire the implementation of Cultural Resource Management, as has been applied to several archaeological sites in Indonesia. With cross-sectoral site management, the CRM model can become a standard guideline for the sustainable development and utilization of the archaeological site of Banten Lama.